A Conditional Reasoning Measure of Goal Orientation : Preliminary Development - Bienkowski, Sarah C. (East Carolina University, 2009)
Self-report measures of goal orientation are susceptible to response distortion, which leads to inaccurate assessments of an individual's goal setting and task choice motivations. Conditional reasoning measures provide an indirect way to assess implicit cognitions associated with personality constructs. In the study, a conditional reasoning measure of goal orientation was preliminarily developed. This measure attempted to indirectly assesses an individual's implicit theory of intelligence, which is the foundation of goal orientation theory. Data were collected from 185 students at a mid-sized southeastern university in the United States. The psychometric properties of the measure were evaluated. Additionally, this study demonstrated a validation process of the new measure, utilizing a series of anagrams as the criterion measure of task choice (persistence) and task performance.
Keywords: Psychology, Personality; Goal orientation; Implicit cognitions; Motivation (Psychology); Goal (Psychology); Self-evaluation; Students--Self-rating of; East Carolina University--Students